Time-dependent non-Hermitian Hamiltonians with real energies - Dutra, Alvaro de Souza [UNESP]; Hott, M. B.; dos Santos, VGCS (Edp Sciences S A, 2005)
In this work we intend to study a class of time-dependent quantum systems with non-Hermitian Hamiltonians, particularly those whose Hermitian counterparts are important for the comprehension of posed problems in quantum optics and quantum chemistry. They consist of an oscillator with time-dependent mass and frequency under the action of a time-dependent imaginary potential. The wave functions are used to obtain the expectation value of the Hamiltonian. Although it is neither Hermitian nor PT symmetric, the Hamiltonian under study exhibits real values of energy.